Ex Libris Prof. Dr Edwarda Rużyłły / Jan Agopsowicz. - Hasso-Agopsowicz, Jan (1915-1982) (1980)
W ozdobnym obramowaniu z kwiatów lilii, trzy tarcze herbowe oraz napis: Ex Libris Prof. Dr Edwarda Rużyłły.